The Future of Labour Justice in the Czech Republic - Jakub Morávek (Societas et Iurisprudentia)
The paper is focused on the general prerequisites of good judiciary. Specifically, the author points out the current problems and shortcomings of the Czech judiciary, such as the length of proceedings, inconsistency in decision-making, and insufficient erudition. He then discusses individual conditions, possibilities and measures that could be used to achieve improvements (prerequisites for performing the function of a judge, specialization, education, involvement of the lay element). In addition, the paper discusses the current draft of law on cancelling the institute of assessors at the labour courts in the Czech Republic. The author presents arguments for maintaining the institute in question, with which he refutes the justification of the draft according to the explanatory memorandum. Along with this, the author suggests a possible suitable form of the institute of assessors.